The Correlation between Empowering by Tutors with Student’s Motivation - Fitri Ayu Natasya; Vevi Sunarti (Universitas Negeri Padang, 2019)
The research was distributed by low motivation citizens learn in following the process of learning, this is allegedly due to lack of skills gives reinforcement by tutors on equality program Package B in the SPNF SKB Padang Panjang City. This type of research using quantitative methods korelasional. The population in this research study program is a citizen equality Package B in the town of Padang Panjang SPNF SKB of 20 people. The number of samples is as many as 15 people. The technique of sampling using stratified random sampling. This research data analysis techniques using percentage and rank order. On the results of the research can be seen that (1) the lack of skills gives reinforcement by tutors, (2) lack of motivation in learning citizens follow the learning process, and (3) there is a significant relationship between the skill of giving reinforcement by tutors with the motivation of learning in the citizens equality Package B in the SPNF SKB Padang Panjang City.Keywords: Reinforcement, Motivation of Learning